If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 75 = 9x + 93 Reorder the terms: 75 + 6x = 9x + 93 Reorder the terms: 75 + 6x = 93 + 9x Solving 75 + 6x = 93 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 75 + 6x + -9x = 93 + 9x + -9x Combine like terms: 6x + -9x = -3x 75 + -3x = 93 + 9x + -9x Combine like terms: 9x + -9x = 0 75 + -3x = 93 + 0 75 + -3x = 93 Add '-75' to each side of the equation. 75 + -75 + -3x = 93 + -75 Combine like terms: 75 + -75 = 0 0 + -3x = 93 + -75 -3x = 93 + -75 Combine like terms: 93 + -75 = 18 -3x = 18 Divide each side by '-3'. x = -6 Simplifying x = -6
| -2+8(x-5)=13x+6-5x | | -3(y-0.5)=0.5 | | -8.978=1.34t | | 3x(2-4)=24 | | -0.67(x+1)=6 | | 4(a-5)+6=2(a-6) | | 8x-3=7(x+5)+4 | | -5s=1.25 | | 3/4x-1=7/5 | | 9x-2=6x+43 | | -3=5(z+7) | | 3X+8Y=30 | | 24=-8y | | 4x^2-19x+24=-2x+9 | | 4x^2-16x+24=-2x+9 | | 12(r-2)=0 | | (8r-64)/4 | | 8r-64/4 | | (X^3+9x^2+7x-24)/(x-2) | | (7/4)x=56 | | 9/1-27/7 | | .5=.5555 | | 12x+3+4x=48 | | 4ax+5ab= | | 6x^5+10x^4-56x^3=0 | | 36/7+X=9 | | 50=-7E-05x^2+0.0164x+0.021 | | 3(6+2y)y=1 | | 3(-8)+4y=20 | | -2(x-6)= | | y=-7E-05x^2+0.0164x+0.021 | | 10x^2+9x-3=0 |